COMPARATIVE STUDY OF TRADITIONAL VS DIGITAL SALES STRATEGIES IN INDUSTRIAL B2B MARKETS - Kumar, Akash; Shewale, Bhojraj; Sharma Padroo, Bhawna (International Journal of Research -GRANTHAALAYAH, 2025)
The Industrial B2B sector has undergone a significant transformation in sales practices over the past decade, driven by increasing digitalization, evolving customer expectations, and competitive market pressures. This research paper presents a comparative analysis of traditional and digital sales strategies within industrial B2B markets, drawing exclusively from secondary data including industry reports, academic journals, and published case studies. Traditional sales strategies—such as personal selling, trade shows, dealer networks, and relationship-driven interactions—have historically dominated industrial markets due to the high-value, technical, and trust-based nature of transactions. However, the rise of digital tools, CRM systems, social selling, automated lead nurturing, and data-driven decision making has redefined how B2B organisations generate leads, engage customers, and close deals. The study analyses the efficiency, cost implications, scalability, customer reach, and long-term impact of both approaches. Findings reveal that while digital sales strategies significantly enhance reach, data accuracy, and conversion efficiency, traditional strategies continue to play a crucial role in relationship-building and high-stakes technical sales. The results indicate that the most effective model is a hybrid sales ecosystem that integrates the personalized strength of traditional selling with the scalability and analytical power of digital channels. The paper concludes that industrial B2B firms must adopt a blended approach to remain competitive, optimise sales productivity, and meet evolving customer expectations in a rapidly digitalizing marketplace.